Inspecting the collective behaviours : a survey for football teams - Manuel Clemente, Filipe (2016)
The collective behaviour on football teams has been widely studied in the last few years, after decades of a deeper study about the technical and physical demands of the football. Now a days a new approach for the match analysis has been possible using the new technological advances from the multiplayer tracking systems. Therefore, the aims of this study is to provide a summarized analysis of the tactical metrics proposed and used in the last few years, trying understand how can these metrics help the match analysis. Thus, the main goal is to provide a practical perspective for the collective behaviour analysis.